2018
DOI: 10.3233/jad-170250
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Biomarkers are Differentially Related to Structural and Functional Changes in Dementia of the Alzheimer’s Type

Abstract: The two cardinal pathologies of Alzheimer's disease (AD) develop according to distinct anatomical trajectories. Cerebral tau-related pathology first accumulates in the mesial temporal region, while amyloid-related pathology first appears in neocortex. The eventual distributions of these pathologies reflect their anatomical origins. An implication is that the cardinal pathologies might exert preferential effects on the structurofunctional brain changes observed in AD. We investigated this hypothesis in 39 patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The DMN is the most vulnerable network to amyloid deposition (Buckner et al, 2005; Shin et al, 2010; Sperling et al, 2009), showing abnormalities in multiple modalities (Grothe & Teipel, 2016). Precuneus and posterior cingulate cortex, as the key nodes in the DMN, also are highly vulnerable to various pathological changes (Gordon et al, 2018; Malpas et al, 2018), which was further confirmed in this study. Compared with the entire brain level, in the brain region of the DMN, the metabolism, spontaneous activity, and energy–oxygen coupling are related to the global Aβ deposition.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The DMN is the most vulnerable network to amyloid deposition (Buckner et al, 2005; Shin et al, 2010; Sperling et al, 2009), showing abnormalities in multiple modalities (Grothe & Teipel, 2016). Precuneus and posterior cingulate cortex, as the key nodes in the DMN, also are highly vulnerable to various pathological changes (Gordon et al, 2018; Malpas et al, 2018), which was further confirmed in this study. Compared with the entire brain level, in the brain region of the DMN, the metabolism, spontaneous activity, and energy–oxygen coupling are related to the global Aβ deposition.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we examined 62 right-handed and Mandarin-speaking subjects with ages ranging 50-79 years, comprising 27 NC subjects, 20 preADs, and 15 CI patients. The data were obtained from the Sino Longitudinal Study on Cognitive Decline (SILCODE) project (Li, Wang, Su, Hu, & Han, 2019) (ClinicalTrials.gov Identifier #NCT03370744).…”
Section: Subjectsmentioning
confidence: 99%
“…The DMN module is the network most susceptible to amyloid accumulation [ 27 ]. Therefore, a common hypothesis is that the DMN network module region is the preferred target for ad-related pathological processes, including Aβdeposition [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DMN module is the network most susceptible to amyloid accumulation [ 27 ]. Therefore, a common hypothesis is that the DMN network module region is the preferred target for ad-related pathological processes, including Aβdeposition [ 27 ]. The correlation between FDG-SUVR and ReHo values in the DMN network gradually decreases with the increasing accumulation of amyloid [ 13 ].…”
Section: Discussionmentioning
confidence: 99%